INTEGRATING LEGAL AND SOCIOCULTURAL STRATEGIES TO ADDRESS WORKPLACE GENDER INEQUALITY IN PONTIANAK - Hazilina, Hazilina; Soedagoeng, Gembongseto Hendro (TANJUNGPURA LAW JOURNAL, 2025)
Abstract This study explores the multifaceted issue of workplace gender inequality in Pontianak by integrating legal and sociocultural approaches to address the persistent challenges faced by women. Despite the presence of legal frameworks such as Law No. 13 of 2003 on Labor and Law No. 21 of 2007 on the Eradication of the Crime of Trafficking in Persons, enforcement remains inconsistent, and gender-specific barriers, such as the "child penalty" and limited leadership opportunities, persist. The study highlights the importance of harmonizing legal strategies, such as strengthened enforcement mechanisms and inclusive policies, with sociocultural interventions aimed at challenging traditional gender norms. Using a contextual approach, this research draws lessons from international best practices, including Kazakhstan"™s labor laws, while emphasizing the need for localized solutions tailored to Pontianak"™s unique socio-economic and cultural dynamics. Key recommendations include enhancing legal accountability, introducing mandatory paternity leave, promoting gender diversity in leadership, and leveraging community-driven programs to foster cultural shifts. The findings underscore the critical role of collaboration between policymakers, civil society organizations, and the private sector in implementing sustainable strategies to bridge the gender gap. By integrating legal and sociocultural strategies, this study provides actionable insights to create an equitable workplace environment, empowering women while contributing to Pontianak"™s socio-economic development. Abstrak Penelitian ini mengeksplorasi isu multifaset terkait ketimpangan gender di tempat kerja di Pontianak dengan mengintegrasikan pendekatan hukum dan sosiokultural untuk mengatasi tantangan yang dihadapi oleh perempuan. Meskipun kerangka hukum seperti Undang-Undang No. 13 Tahun 2003 tentang Ketenagakerjaan dan Undang-Undang No. 21 Tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang telah ada, pelaksanaannya masih kurang konsisten, sementara hambatan gender seperti "child penalty" dan keterbatasan akses perempuan ke posisi kepemimpinan tetap menjadi masalah yang signifikan. Penelitian ini menyoroti pentingnya harmonisasi strategi hukum, seperti penguatan mekanisme penegakan hukum dan kebijakan yang inklusif, dengan intervensi sosiokultural yang bertujuan untuk mengubah norma-norma gender tradisional. Dengan pendekatan kontekstual, penelitian ini mengambil pelajaran dari praktik terbaik internasional, termasuk kerangka kerja hukum tenaga kerja Kazakhstan, sambil menekankan perlunya solusi lokal yang disesuaikan dengan dinamika sosial, ekonomi, dan budaya unik di Pontianak. Rekomendasi utama meliputi peningkatan akuntabilitas hukum, pengenalan kebijakan cuti ayah wajib, promosi keberagaman gender dalam kepemimpinan, serta pemanfaatan program berbasis komunitas untuk mendorong perubahan budaya. Hasil penelitian ini menekankan peran penting kolaborasi antara pembuat kebijakan, organisasi masyarakat sipil, dan sektor swasta dalam menerapkan strategi berkelanjutan untuk menjembatani kesenjangan gender. Dengan mengintegrasikan pendekatan hukum dan sosiokultural, penelitian ini memberikan wawasan praktis untuk menciptakan lingkungan kerja yang adil, memberdayakan perempuan, dan berkontribusi pada pembangunan sosial ekonomi di Pontianak.